2021
DOI: 10.3390/cancers13215400
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Novel Small Molecular TRPM4 Inhibitors in Colorectal Cancer Cells

Abstract: (1) Background: Transient receptor potential melastatin (TRPM4) ion channel aberrant expression or malfunction contributes to different types of cancer, including colorectal cancer (CRC). However, TRPM4 still needs to be validated as a potential target in anti-cancer therapy. Currently, the lack of potent and selective TRPM4 inhibitors limits further studies on TRPM4 in cancer disease models. In this study, we validated novel TRPM4 inhibitors, CBA, NBA, and LBA, in CRC cells. (2) Methods: The potency to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…At a concen-tration of 50 µM, NBA and LBA blocked approximately 90 and 85% of the endogenous TRPM4 currents in DU145 cells, but neither compound influenced the proliferation and migration of these cells [132]. HCT116 cells were more sensitive than LNCaP cells, as complete and irreversible TRPM4 inhibition could be achieved by all three drugs [133]. It seems that although CBA, NBA, and LBA are very potent inhibitors of TRPM4, their effect is less pronounced in cells that have endogenous TRPM4 channels than in those with overexpressed ones.…”
Section: Cba and Other Related Compounds (Lba And Nba)mentioning
confidence: 95%
See 1 more Smart Citation
“…At a concen-tration of 50 µM, NBA and LBA blocked approximately 90 and 85% of the endogenous TRPM4 currents in DU145 cells, but neither compound influenced the proliferation and migration of these cells [132]. HCT116 cells were more sensitive than LNCaP cells, as complete and irreversible TRPM4 inhibition could be achieved by all three drugs [133]. It seems that although CBA, NBA, and LBA are very potent inhibitors of TRPM4, their effect is less pronounced in cells that have endogenous TRPM4 channels than in those with overexpressed ones.…”
Section: Cba and Other Related Compounds (Lba And Nba)mentioning
confidence: 95%
“…Compared to CBA, NBA and LBA were even more potent on TRPM4 channels expressed in HEK cells (IC 50 values were 0.4 and 1.6 µM, respectively). In the case of native TRPM4 channels, NBA was the most potent blocker, with an IC 50 of 0.13 µM in the HCT116 colorectal cancer cell line [133], while LBA was slightly less potent compared to CBA (IC 50 values of 1.84 and 1.17 µM, respectively). Regarding their specificity, 10 µM NBA influenced glucagon-like peptide receptor 1, while 10 µM NBA slightly potentiated TRPM5 currents [78].…”
Section: Cba and Other Related Compounds (Lba And Nba)mentioning
confidence: 96%
“…Our data show a recovery of the viability and cell cycle shift in cells expressing functional TRPM4, while the pore mutant was not able to rescue this phenotype. [52,53] All this points to TRPM4 conductivity as an underlying mechanism for the contribution of TRPM4 to cancer hallmarks. In both PCa and CRC cells, Na + current through TRPM4 is a negative feedback mechanism for store-operated Ca 2+ entry (SOCE).…”
Section: Compounds In Cancer Hallmark Functionsmentioning
confidence: 99%
“…A TRPM4-mediated decrease in Ca 2+ entry has been observed in various cellular systems, including immune, cancer, cardiac muscle, and dental pulp cells [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]; however, other groups have found that TRPM4 mediates an increase in Ca 2+ entry [ 12 , 13 , 14 ]. The aberrant expression or malfunction of TRPM4 has been characterized in multiple diseases, such as cardiovascular [ 15 , 16 , 17 ], neurological [ 18 ], and skin diseases [ 19 ], as well as in different types of cancer [ 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Furthermore, TRPM4 plays a role in various immune cell functions [ 3 , 11 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that TRPM4 is the main source of Ca 2+ -activated Na + entry in the colorectal cancer (CRC) cell line HCT116 and that TRPM4 ion conductivity is involved in the regulation of cellular functions, such as cell viability and cell cycle in different CRC cells [ 29 , 32 ]. TRPM4 is controlled by p53, and the loss of p53 function in late-stage CRC cancer may enhance the role of TRPM4 in CRC progression [ 54 ].…”
Section: Introductionmentioning
confidence: 99%